Imaging potential geothermal resources in the Hengill volcanic area (Iceland) with active-source seismics recorded by a dense nodal array - Gyger, Lea; Sánchez Sánchez-Pastor, Maria Del Pilar; id_orcid:0 000-0002-1163-5488; Maurer, Hansruedi; Obermann, Anne; id_orcid:0 000-0001-6933-6301; Wiemer, Stefan; id_orcid:0 000-0002-4919-3283 (Copernicus, 2022)
The Hengill area, located a few km west of Reykjavik, is situated on the triple junction of three large geological features: the onshore section of the Mid-Atlantic Ridge, called the Reykjanes Peninsula Oblique Rift, the Western Volcanic Zone and the South Iceland Seismic Zone. This area hosts two large-scale geothermal power plants, Nesjavellir and Hellisheiði. Both are producing electricity and hot water. Hengill is also one of the targets of the Iceland Deep Drilling Project that aims at finding and exploiting supercritical fluids. In summer 2021, a nodal network of 500 5 Hz geophones was deployed in the area over a period of 2 months. It complemented seismic data from a network of broadband stations that were already deployed earlier. In July 2021, a vibroseis experiment was conducted in the area in form of two surveys performed by a fully electrical seismic vibrator truck. The seismic waveforms were recorded by parts of the nodal network. In this study, we focus on the survey conducted along the road leading to the Nesjavellir geothermal power plant, in Mosfellsheiði. The aim of the survey in Mosfellsheiði is to obtain new insights on a low-velocity anomaly as well as on a yet poorly understood seismic cluster that has been detected in the area by previous studies. To study the velocity and attenuation structure of the area, we computed a first arrival travel time tomography and an attenuation profile. Finally, we compared our results with an existing 3D seismic ambient noise tomography Vs model of the area as well as with known local subsurface properties, such as resistivity and mineralogy. The final results of this vibroseis study could be useful for finding new geothermal resources in the Nesjavellir area.